THE STRATEGIES OF ISLAMIC BOARDING SCHOOL TO REDUCE ACADEMIC STRESS AMONG STUDENT DURING COVID-19 PANDEMIC - Safiruddin Al Baqi; Kharisul Wathoni (Proceeding International Seminar of Islamic Studies, 2022)
Academic stress should became the concern for school management, because it could affect the various things, mainly student achievement. Covid-19 become one of the source of stress not only for students but also for all societies. This study aims to determine the reasons of academic stress in Islamic boarding school students and to find out the method to deal with it. This study used qualitative research methods with a case study approach. The subjects of this study were six students of two Islamic boarding schools in Ponorogo, East Java. The results of this study indicate that several factors influence the academic stress of Islamic boarding school students, including lack of access to outside the school or dormitory environment which makes students feel homesick, feeling bored with their routines, and worries about getting sick because it will have an impact on isolation. This reasons made it difficult for students to focus on learning so that solutions were needed to reduce their academic stress. The strategy used by Islamic boarding schools is provide interesting activities for students, such as sports, artistic activities, language development, and others. So that the academic stress among students can be reduced or even prevented.Keywords: Academic Stress, Covid-19, Islamic Boarding School, Student.